Auditor Workload and Audit Quality: The Mediating Roles of Fatigue and Burnout Among Apip Auditors in Maluku - Zulkipli Zulkipli; Pranatalindo Simanjuntak; Muhammad Iqbal; Riman Abimanyu; Robby Erviando (JUEB : Jurnal Ekonomi dan Bisnis, 2026)
This study examines the effect of auditor workload on audit quality, with fatigue and burnout as mediating variables, in the context of Government Internal Auditors (APIP) in Maluku, Indonesia. An exploratory quantitative approach was employed using survey data from 133 APIP auditors through a census technique. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS, including assessment of the measurement and structural models as well as mediation testing through bootstrapping. The results show that auditor workload has a negative effect on audit quality (β = -0.367), while positively influencing fatigue (β = 0.388) and burnout (β = 0.261). In addition, both fatigue (β = -0.403) and burnout (β = -0.299) reduce audit quality. Mediation analysis confirms that fatigue and burnout partially mediate the relationship between workload and audit quality.These findings indicate that excessive workload not only directly reduces audit quality but also indirectly weakens it through deteriorating psychological well-being. This study contributes to the audit literature by integrating psychological factors into the workload on audit quality relationship and providing empirical evidence from the understudied context of government internal auditors in Indonesia.